PERANAN LEMBAGA AMIL ZAKAT INFAQ DAN SHODAQOH DI MASJID AL MUHAJIRIN KOMPLEK DEPLU CARAKA BHUWANA DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT SEKITAR - Maman; Irvan Iswandi; Ali Aminulloh (Jurnal Penelitian Multidisiplin Ilmu, 2023)
In zakat there are two dimensions of worship, namely the vertical dimension which is the relationship between Muslims and Allah SWT, and the horizontal dimension where a Muslim will always be in touch with other Muslims. The purpose of this study was to determine the practice of receiving zakat infaq and shodaqoh at the Al Muhajirin Mosque, Complex of the Ministry of Foreign Affairs, Caraka Bhuwana, and to determine the role of the amil zakat, infaq and shodaqoh institutions at the Al Muhajirin Mosque, Complex, Ministry of Foreign Affairs, Caraka Bhuwana, in improving the community's economy. This study uses a qualitative approach. This type of research is field research and the nature of the research uses a descriptive approach. Sources of research data are primary data sources and secondary data. Data collection techniques in this study were observation, interviews and documentation. The results of the study 1) The practice of managing zakat infaq and shodaqoh at the Al Muhajirin Mosque, Complex of the Ministry of Foreign Affairs, Caraka Bhuwana, is quite good by using management principles, namely planning, organizing, implementing and supervising. 2) The role of the amil zakat infaq and shodaqoh institutions at the Al Muhajirin Mosque, namely: (1) in the religious sector, providing assistance to Koran teachers and Al-Quran assistance to children. (2) in the education sector, namely providing educational scholarships (3) in the economic sector, namely providing financial assistance for small businesses.